Uncertainty and Economic Activity: A Global Perspective - Ambrogio Cesa-Bianchi; M. Hashem Pesaran; Alessandro Rebucci (Center for Economic Studies and ifo Institute (CESifo), 2014)
The 2007-2008 global financial crisis and the subsequent anemic recovery have rekindled academic interest in quantifying the impact of uncertainty on macroeconomic dynamics based on the premise that uncertainty causes economic activity to slow down and contract. In this paper, we study the interrelation between financial markets volatility and economic activity assuming that both variables are driven by the same set of unobserved common factors. We further assume that these common factors affect volatility and economic activity with a time lag of at least a quarter. Under these assumptions, we show analytically that volatility is forward looking and that the output equation of a typical VAR estimated in the literature is mis-specified as least squares estimates of this equation are inconsistent. Empirically, we document a statistically significant and economically sizable impact of future output growth on current volatility, and no effect of volatility shocks on business cycles, over and above those driven by the common factors. We interpret this evidence as suggesting that volatility is a symptom rather than a cause of economic instability.
Keywords: E44; F44; G15; 330; uncertainty; realized volatility; GVAR; great recession; identification; business cycle; common factors